The Haunted Puerto Rican Stage: Lucy Boscana in La carreta and Vejigantes - Stevens, Camilla (Latin American Theatre Review, 2004)
This article examines the figure of Lucy Boscana who was cast as counterpoint archetypal mothers of the national family in René Marqués’s La carreta (1952) and Francisco Arriví’s Vejigantes (1958). I contend that Lucy Boscana’s repeat performances – over 800 of them – of the jíbara mother Doña Gabriela haunts the Puerto Rican stage to the extent that it eclipses the Afro-Puerto Rican mother Mamá Toña in the Puerto Rican cultural memory. My argument considers the use of blackface and the construction of the female body as object of the male gaze as central factors in the erasure of black subjectivity from the Puerto Rican stage. (CS)